2008
DOI: 10.1007/s10535-008-0125-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity assessment in Portugal accessions of Olea europaea by RAPD markers

Abstract: Eighty seven olive (Olea europaea ssp. sativa L.) cultivar accessions from Portugal were characterized by means of randomly amplified polymorphic DNA (RAPD) markers. Of the 11 arbitrary 10-mer primers tested a total of 92 polymorphic bands were obtained, representing 87.6 % of the total amplification products. Twenty nine different genotypes were clearly discriminated. Differences were not found among the amplification profiles from different individuals of the same cultivar. All the genotypes could be identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
(31 reference statements)
0
21
0
1
Order By: Relevance
“…Using RAPD markers, cultivars from restricted areas were grouped according to geographical origin, but without evident clustering based on fruit size or other morphological traits (Sanz-Cortez et al, 2001). In the Mediterranean basin, RAPD profiles were correlated with the use of fruits and the country of origin, suggesting a selection scheme from different genetic pools in different areas (Besnard et al, 2001;Cordeiro et al, 2008;Rugini et al, 2011). Sarri et al (2006), using SSR markers, found limited grouping according to geographic origin and grouped olive cultivars as eastern, central and western Mediterranean populations.…”
Section: Genetic Relationships Among Olive Cultivarsmentioning
confidence: 98%
See 2 more Smart Citations
“…Using RAPD markers, cultivars from restricted areas were grouped according to geographical origin, but without evident clustering based on fruit size or other morphological traits (Sanz-Cortez et al, 2001). In the Mediterranean basin, RAPD profiles were correlated with the use of fruits and the country of origin, suggesting a selection scheme from different genetic pools in different areas (Besnard et al, 2001;Cordeiro et al, 2008;Rugini et al, 2011). Sarri et al (2006), using SSR markers, found limited grouping according to geographic origin and grouped olive cultivars as eastern, central and western Mediterranean populations.…”
Section: Genetic Relationships Among Olive Cultivarsmentioning
confidence: 98%
“…Prior studies using molecular techniques have shown a clustering of olive cultivars based on their morphological traits and fruit use (Besnard et al, 2001;Rotondi et al, 2003;Baldoni et al, 2006;Cordeiro et al, 2008;Fendri et al, 2010). Those genetic relationships may reflect the selection pressure for agronomic and fruit quality characters.…”
Section: Genetic Relationships Among Olive Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenological and reproductive biology of this species has been the focus of several studies aimed at identifying self-compatible cultivars and assessing rates of self-sterility (Albertini et al, 2011). Most modern olive cultivars are believed to have been obtained from the crossing of wild plants followed by focused human selection (Cordeiro et al, 2008), resulting in the generation of hundreds of cultivars over a period of centuries. Because of the large number of olive cultivars and their narrow genetic diversity, which is a function of geographic proximity, varietal synonyms and homonyms frequently occur, which raise several problems for germplasm management and preservation (Hakim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For the bryophytes there have been a few, but very valuable contributions up to date (Shaw & Schneider 1995;Bischler & Boisslelier-Dubayle 1997;Wyatt et al 1997;Cronberg 2000;Shaw 1995Shaw , 2000Shaw , 2001Chiang & Schaal 1999;McDaniel & Shaw 2003;Skotnicki et al 2004) Lately, there is increasing interess on genetic diversity of both, wild and cultivated plants and its varieties (eg. Narasimhan et al 2006;Padmesh et al 2006;Joshi & Dhawan 2007, Refoufi & Esnalut 2008Yao et al 2008;Cordeiro et al 2008;Choudhury et al 2008;), but there is very few studies on cryptogams incl. bryophytes (e. g. van der Velde & Bijlsma 2003;Werner & Guerra 2004;Sabovljević et al 2005Sabovljević et al , 2006Spagnuolo et al 2007Spagnuolo et al , 2008Grundmann et al 2008, 2009).…”
Section: Introductionmentioning
confidence: 99%